Plague fighter the autobiography of a modern Chinese physician - Wu, Liande 1879-1960 (Areca Books, 2014)
In this book, originally published in 1959, a year before his death, Dr Wu takes the reader through his extraordinary life from being born in Penang to becoming the first person of Chinese descent to graduate in medicine from Cambridge University and then to changing the face of medicine in China at the start of the 20th century. Arguably he could also claim credit for being the first Chinese doctor to demonstrate the effectiveness of modern medicine in the country as his research helped halt the Manchurian Plague. He was the first president of the Chinese Medical Association and established twenty medical institutions in China. 672 pages with appendices, Dr Wu's obituary in the Times newspaper and indices of Chinese and Non-Chinese people mentioned in the text.